Baroreflex Sensitivity, Cardiac and Kidney Remodeling and Deterioration in Vasoactive Substances Content in Blood in Experimental Model of Renovascular Hypertension. Action of Natural Flavone, Luteolin - N.A. Papiashvili; M.V. Ghonghadze; N.V. Sharikadze; M. P. Khutsishvili; K.A. Bakuridze; A.J. Bakuridze; G.V. Sukoyan; N.V. Gongadze (Journal of Nephrology Advances, 2023)
This study aimed to analyze pharmacological actions of phenolic compound luteolin on the renal and cardiac hypertrophy, blood pressure (BP), baroreflex sensitivity (BRS), levels of epoxyeicosatrienoic acids (EETs), prostaglandin E-2 (PGE-2) and endothelin-1 (E1) in plasma in the 2 kidney - 1 clip (2K-1C) model of renovascular hypertension (RVH). All animals, were randomized into 2 groups: control (normal) I - sham-operated, II- RVH male Wistar rats, which after 4 weeks of surgical intervention secondly randomized to control II group, treated 0.1% dimethyl sulphoxide (DMSO) and main group - with luteolin in 15 DMSO, 3 mg/kg body weight, intraperitonially, during 2 weeks. ET-1, EETs and PGE2 levels investigated in carotid artery blood plasma and analyzed using ELISA kits. All data statistically analyzed using the SPSS-10.0 program. In RVH rats BP increased by 32%, cardiac and right kidney hypertrophy and reduction in parasympathetic component of BRS by 40% and sympathetic by 39%. The plasma level of total trans-EETs and PGE2 in RVH rats decreased by 44% and 50% respectively, while the level of ET-1 increased by 67%. Two weeks treatment with luteolin lowered BP, improved parasympathetic, without marked changes in sympathetic component of BRS. Deremodeling of cardiac and renal hypertrophy under prolonged treatment with luteolin accompanied with increasing in the level of EETs by 44%, PGE-2 by 50% and markedly reducing of plasma content of ET-1 (by 60%). Inhibition of EET hydrolase using low doses of luteolin provides beneficial cardio and renoprotective action in experimental model of RVH.
Keywords: Renovascular Hypertension